ILLEGAL TRADE IN HUMAN ANATOMICAL MATERIALS (PART. 4 OF ARTICLE 143 OF THE CRIMINAL CODE OF UKRAINE): SOME ISSUES OF ANALYSIS OF THE SUBJECT OF CRIME (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the problem of understanding the place of blood and its components as a part of the subject of a criminal offence provided for in Part 4 of Art. 143 of the Criminal Code of Ukraine. The conducted research directly affects both the features of the specified norm and the analysis of relevant provisions of other domestic special legislation. A certain place in the work is given to the understanding of blood and its components in general and specialised reference sources. According to the results of the study, a conclusion was formulated about the urgent need to properly determining the place of blood and its components in the system of legal support for its circulation.
Keywords: transplantation; anatomical materials; tissues; blood; blood components; illegal trade in anatomical materials